Neutrophil stimulation with citrullinated histone H4 slows down calcium influx and reduces NET formation compared with native histone H4. - Lai Shi; Karen Aymonnier; Denisa D Wagner (PLoS ONE)
Peptidylarginine deiminase 4 (PAD4) catalyzes posttranslational modification of many target proteins through converting protein arginine or mono-methylarginine to citrulline. Neutrophil extracellular trap (NET) formation is the most dramatic manifestation of PAD4-mediated hypercitrullination reaction in neutrophils, which is characterized by the release of nuclear chromatin to form a chromatin network in the extracellular space. Histones H4, one of the major protein components of chromatin, is released into the extracellular space during sepsis, trauma, and ischemia-reperfusion injury and can also be released during the process of NET formation, along with its citrullinated form. The present study showed that histone H4 can induce NET formation in a calcium and PAD4 dependent manner. Histone H4 caused permeabilization of the neutrophil membrane and sustained rise in intracellular calcium that is necessary for activation of PAD4. In comparison, citrullinated histone H4 induced less calcium influx compared with its native form, leading to reduced NET formation. These studies suggest that citrullinated histone H4 could serve as a brake in the pathology of NETs, slowing down the vicious circle between histone H4 and NETs.